Early Phases of COVID-19 Are Characterized by a Reduction in Lymphocyte Populations and the Presence of Atypical Monocytes - Lombardi, Andrea; Trombetta, Elena; Cattaneo, Alessandra; Castelli, Valeria; Palomba, Emanuele; Tirone, Mario; Mangioni, Davide; Lamorte, Giuseppe; Manunta, Maria; Prati, Daniele; Ceriotti, Ferruccio; Gualtierotti, Roberta; et al. (Frontiers in Immunology, 2020)
Background Severe acute respiratory syndrome coronavirus 2 is a recently discovered pathogen responsible of coronavirus disease 2019 (COVID-19). The immunological changes associated with this infection are largely unknown. Methods We evaluated the peripheral blood mononuclear cells profile of 63 patients with COVID-19 at diagnosis. We also assessed the presence of association with inflammatory biomarkers and the 28-days mortality. Results Lymphocytopenia was present in 51 of 63 (80.9%) patients, with a median value of 720 lymphocytes/µL (IQR 520-1,135). This reduction was mirrored also on CD8+ (128 cells/µL, IQR 55-215), natural killer (67 cells/µL, IQR 35-158) and natural killer T (31 cells/µL, IQR 11-78) cells. Monocytes were preserved in total number but displayed among them a subpopulation with a higher forward and side scatter properties, composed mainly of cells with a reduced expression of both CD14 and HLA-DR. Monocytes count was unrelated to IL-6 serum values (R= 0.012, p= 0.06). Patients who died in the 28 days from admission (N=10, 15.9%), when compared to those who did not, displayed lower mean values of CD3+ (337.4 cells/µL vs 585.9 cells/µL; p=0.028) and CD4+ cells (232.2 cells/µL vs 381.1 cells/µL; p=0.042) and an higher percentage of CD8+/CD38+/HLA-DR+ lymphocytes (13.5% vs 7.6%; p=0.026). Discussion The early phases of COVID-19 are characterized by lymphocytopenia, predominance of Th2-like lymphocytes and monocytes with altered immune profile, which include atypical mononuclear cells.